The State of Our Unions: Exploring Relationship Quality among Dyadic Couple Homeowners. Issue 1 (2nd January 2020) - Harris, Victor W.; Visconti, Brian; Sewell, Charles B.; Cantrell, Randy; Anderson, Jon; Toelle, Stephanie
Abstract: Relationship stability represents a major economic interest not only to Florida, but to every state in the nation. The cumulative expenses related to relationship dissolution (including litigation costs, foregone tax revenues, and federal assistance programs such as Medicaid, child welfare SCHIP, TANF, WIC and SNAP) are estimated to cost taxpayers billions annually. Overall detriments are also higher when considering longitudinal impacts of family instability on affected couples and children in terms of lost productivity and psychosocial impact. This study endeavors to better understand threats to family instability, relationship quality and contextual factors via data collected from a sample of Florida homeowners in three types of cohabiting relationships. Analysis shows that roughly 60% of the variability in relationship quality is accounted for by negative interaction and consensus scores. High measures of negative interaction among dyadic couples indicate that cohabiting relationships in Florida are significantly distressed. Implications for how residents of Florida and other states could benefit both economically and psychosocially from implementation of couple and relationship education (CRE) programs are discussed.